Updates in the Diagnosis of Chronic Pancreatitis: Current Approaches and New Possibilities - Vanek, Petr; Freeman, Martin L (Gastroenterology clinics of North America, 2025)
This review provides a comprehensive update on the diagnostic approaches to chronic pancreatitis (CP), emphasizing recent advancements in imaging techniques, biomarker research, and multivariable scoring systems. Despite substantial progress in these areas, current diagnostic algorithms have limitations, particularly for early and non-calcific CP. Traditional criteria have focused on classic diagnostic signs, but "minimal change" CP is increasingly recognized through advanced imaging and function tests. This article aims to guide clinicians in applying current methods and available strategies for CP diagnosis and outline research efforts in the field.
Keywords: algoritmy; Imaging; chronická pankreatitida; Diagnostic criteria; Pancreatic function tests; Pancreatitis, Chronic; Humans; biologické markery; Chronic pancreatitis; lidé; Biomarkers; Algorithms; Pancreatic Function Tests; Diagnosis; funkční testy pankreatu